Interests of Korean Tourists Traveling Abroad and Actions Required in Barcelona - Espinosa, Silvia Mirabet; Kang, Sin Gyu (Asian Journal of Empirical Research, 2020)
The number of Korean tourists has increased significantly in Barcelona, Spain. The article has two objectives: firstly, to determine the context, reasons for travelling abroad and tastes of Koreans as potential tourists so that Barcelona tourism industry may plan its activities or business lines in accordance with great continuously growing Korean demand. Secondly, to establish guidelines for actions required to adapt destination towards Korean demand. We first conducted bibliographic analysis to gather economic data on Korean tourism to fulfil these dual objectives. The data was taken from various reports compiled by different economic institutions in both countries as reflected in this study that communication is the factor that worries Korean tourists the most. Secondly, they are not sure about local food, inter-city public transport, travelling expenses, poor quality and poorly located accommodation, lack of clean public toilets, etc. in Barcelona, In contrast, Koreans love to travel to Barcelona to make luxury purchases in emblematic places by setting aside other concerning factors.